Revise of the Law Exclusive Economic Zone in Indonesia: An Urgent Necessity - Pramono, Agung; Adriano, Adriano (Hang Tuah Law Journal, 2023)
Indonesia is an archipelago with massive oceans. In 1982, the United Nations Convention on the Law of the Sea (UNCLOS) was signed in Jamaica. In 1983 the Indonesian government passed Law Number 5 of 1983 concerning Exclusive Economic Zone, and UNCLOS 1982 was set as one of the fundamental considerations in the Law. However, the issue is what is the legal basis of including the UNCLOS 1982 as one of the basic considerations and how these two laws are related. This research employed a normative method aiming to study one of the fundamental considerations of the making of Law Number 5 of 1983 concerning the Exclusive Economic Zone in Indonesia. The results of the discussion show that the inclusion of UNCLOS 1982 as a basis for consideration in making Law Number 5 of 1983 concerning Indonesia's EEZ is problematic from the legal position of the rules. Law Number 5 of 1983 concerning the EEZ of Indonesia needs to be revised by referring to Law Number 17 of 1985 concerning the Ratification of the Convention of The Law of the Sea. This revision is intended to improve the regulation concerning the implementation of sovereign rights and jurisdiction and related regulatory provisions regarding the EEZ of Indonesia in terms of the interest of security on the sea.